2011
DOI: 10.1517/14656566.2011.566558
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan and bevacizumab in recurrent glioblastoma multiforme

Abstract: BVZ + irinotecan leads to high RR and to an increased 6-month progression-free survival. However, no improvement in median overall survival has been observed compared with conventional chemotherapy. Nevertheless, the GBM patients who respond to treatment with BVZ and irinotecan have survived significantly longer than non-responders, indicating that it could be beneficial for a selection of patients to receive this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 77 publications
1
21
0
Order By: Relevance
“…The reason for this result remains unclear, with one possibility being that bevacizumab decreases interstitial pressure, improves tissue oxygenation and increases the delivery of irinotecan to the tumour. 33 However, our meta-analysis showed that adding irinotecan to bevacizumab did not result in additional improvement in OS when compared with bevacizumab only; and this conclusion was consistent with Friedman et al 19 The toxicity of these treatment protocols should also be considered. In several meta-analyses, bevacizumab was reported to be associated with many side effects, including venous thromboembolism, 34 bleeding 35 and gastrointestinal perforation.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for this result remains unclear, with one possibility being that bevacizumab decreases interstitial pressure, improves tissue oxygenation and increases the delivery of irinotecan to the tumour. 33 However, our meta-analysis showed that adding irinotecan to bevacizumab did not result in additional improvement in OS when compared with bevacizumab only; and this conclusion was consistent with Friedman et al 19 The toxicity of these treatment protocols should also be considered. In several meta-analyses, bevacizumab was reported to be associated with many side effects, including venous thromboembolism, 34 bleeding 35 and gastrointestinal perforation.…”
Section: Discussionsupporting
confidence: 87%
“…3,[8][9][10] More than half of patients, however, fail to respond and many of the responders inevitably develop resistance to therapy. 11,12 Therefore, identification of patient subgroups that will preferentially benefit from bevacizumab therapy may help guide therapeutic management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising combinations is the use of Bevacizumab with irinotecan (CPT-11). With this regimen the PFS-6 and OSA is 50% and 8.7 months while with Bevacizumab on its own, the PFS and OAS was 42% and 9.2 months respectively (Jakobsen et al, 2011). In our institute, the choice of salvaging chemotherapy for patients with rGBM is mainly based on their past therapeutic history and the toxicity profile.…”
Section: Antiangiogenic Treatmentmentioning
confidence: 92%